The liar's key - Lawrence, Mark, 1966- (Lawrence, Mark, 1966- Red Queen's war, 2015)
"After harrowing adventure and near-death, Prince Jalan Kendeth and the Viking Snorri ver Snagason find themselves in possession of Loki's Key, an artefact capable of opening any door, and sought by the most dangerous beings in the Broken Empire--including The Dead King. Jal wants only to return home to his wine, women, and song, but Snorri has his own purpose for the key: to find the very door into death, throw it wide, and bring his family back into the land of the living. And as Snorri prepares for his quest to find death's door, Jal's grandmother, the Red Queen, continues to manipulate kings and pawns towards an endgame of her own design"--Dust jacket flap.